Sensual Construction of Body and Biography. Suggestions to Mutually Improve Deficient but Widespread Body Concepts and Biographical Research - Fischer, Wolfram (Qualitative Sociology Review, 2022)
Against the backdrop of an increasing interest in visual methods in social research, this paper examines some theoretical foundations of human (inter-)action by reflecting on the interplay between senses, the body, and biography. The main purpose of the paper is to combine an integral, non-Cartesian concept of the self as body (respectively the lived body as self) with biographical research—thus enriching research on the body, as well as on biography. Criticizing the Cartesian split of body and mind, classical phenomenological (Leib) and recent concepts of the body (“embodiment”) are sketched, resulting in a processual model of the sensual construction of the lived and living body in its environment. Given the interplay of bodily foundations of the self and processes of biographical structuring, so far, distant fields of research are converged. Some suggestions for conceptual improvements, an attentional shift to body aspects, respective research topics, and the extension of methods exceeding the narrative biographical interview in biographical research are indicated.